ANALISIS PENGARUH PROFITABILITAS DAN STRUKTUR KEPEMILIKAN TERHADAP STRUKTUR MODAL DAN KINERJA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Riawan, I Wayan Rio; Artini, Luh Gede Sri (E-Jurnal Manajemen; Vol 3 No 11 (2014), 2014)
Along with the development of drugs and medical devices businesses and hospitals are growing rapidly, so that the performance of the company in this business needs to be improved to know how big the gains from assets, equity, and corporate debt. Therefore, this study using a pharmaceutical company listed on the Indonesia Stock Exchange as the object of study in which the return on equity as a measure of firm performance, Debt to Equity Ratio as a measure of capital structure, management ownership as a measure of ownership structure and net profit margin as a measure of profitability. The data used are secondary data from the period 2005-2012 the annual financial statements. Samples obtained by purposive sampling method with the final number 5 samples. The analysis technique used is the path analysis. The results of the analysis in this study obtained a significant negative effect between NPM and ownership of the DER management, ownership management NPM and significant positive effect on ROE, while DER significantly negatively affect ROE. Based on further analysis of the results obtained by the direct effect is smaller than the total effect, this shows that the use of DER as a mediating variable will improve the management and ownership of NPM influence on ROE.
Keywords: Net Profit Margin, property management, Debt to Equity Ratio, Return on Equity